Decompositions of wage inequality and growth in an advanced economy open to trade - T. Huw Edward; Matthias Lücke (Kiel Institute for the World Economy (IfW), 2011)
We explore the uses of double-calibrated general equilibrium models as a decomposition tool for analysing contributory factors in the growth and increasing wage inequality in an advanced economy (the UK) since 1979. Calibration of a model to start and end years, based upon an assumed functional form and parameter values, produces a consistent set of decompositions for both growth and inequality. Calibrated TFP growth is consistent with the results from nonparametric growth accounting. The calibration procedure also allows us to explore different exogeneity assumptions regarding capital. However, there are more problems to modelling inequality than with growth: in particular, the main models in the literature, which take skill endowments as given, are characteristically unstable. This strongly emphasises the need for a more dynamic modelling technique, particularly regarding the skill acquisition decision and potential labour market mismatch issues.
Keywords: C68; F16; O4; 330; general equilibrium; wage inequality; trade; growth; Lohnstruktur; Lohndifferenzierung; Allgemeines Gleichgewicht; Produktivität; Dekompositionsverfahren; Offene Volkswirtschaft; Theorie